# Solve each of the following quadratic equations:x2 + 6x - (a2 + 2a - 8) = 0

x2 + 6x - (a2 + 2a - 8) = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 1; b = 6 ;c = - (a2 + 2a - 8)

= 1. - (a2 + 2a - 8)

= - (a2 + 2a - 8)

And either of their sum or difference = b

= 6

Thus the two terms are (a + 4) and - (a - 2)

Difference = a + 4 - a + 2

= 6

Product = (a + 4) - (a - 2)

= - (a2 + 2a - 8)

x2 + 6x - (a2 + 2a - 8) = 0

x2 + (a + 4)x - (a - 2)x - (a + 4)(a - 2) = 0

x [x + (a + 4)] - (a - 2) [x + (a + 4)] = 0

[x + (a + 4)] [x - (a - 2)] = 0

[x + (a + 4)] = 0 or [x - (a - 2)] = 0

x = - (a + 4) or x = (a - 2)

Hence the roots of equation are - (a + 4) or (a - 2)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic EquationsFREE Class
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Balance the Chemical Equations49 mins
Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses